The photography of Victorian Scotland - Simpson, Roddy (Edinburgh University Press, 2012)
This title provides a full and coherent introduction to the photography of Victorian Scotland. The material has been structured and the topics organised, with appropriate illustrations, as both a readable narrative and a foundation text for the subject.